Determinasi Kualitas Laporan Keuangan Bank Syariah: Peran Opini Audit, Audit Delay, dan Profitabilitas - Zahrina Sazida Afra; Sri Rahayu; Zufrizal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to examine the effect of audit opinion and audit delay on financial reporting quality with profitability as a moderating variable in Islamic Commercial Banks during the 2022–2024 period. This research employed a quantitative approach using secondary data obtained from annual financial statements. The sample was determined using purposive sampling, resulting in 33 observations. Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS version 25. The results reveal that audit delay has a negative and significant effect on financial reporting quality, with a regression coefficient of -0.006 and a significance value of 0.006 (< 0.05). This finding indicates that longer audit completion periods tend to reduce the timeliness and relevance of financial information. Meanwhile, audit opinion does not significantly affect financial reporting quality, as indicated by a significance value of 1.000 (> 0.05). Simultaneously, audit opinion and audit delay significantly affect financial reporting quality, with an F-statistic value of 4.533 and a significance level of 0.019 (< 0.05). Furthermore, the coefficient of determination test shows an R Square value of 0.232, indicating that 23.2% of the variation in financial reporting quality can be explained by the independent variables, while the remaining 76.8% is influenced by other factors outside the research model. The findings also demonstrate that profitability is unable to moderate the relationship between audit opinion and audit delay on financial reporting quality because the interaction variables show significance values above 0.05. This study contributes to the literature on Islamic banking and financial reporting quality by emphasizing the importance of audit efficiency in enhancing the credibility and timeliness of financial reporting in Islamic financial institutions.